1986
DOI: 10.1246/cl.1986.1781
|View full text |Cite
|
Sign up to set email alerts
|

Octamethyltetrasila[2.2]paracyclophane. Cyclophanes Bridged by Polysilanes

Abstract: 1,1,2,2,9,9,10,10-Octamethyl-1,2,9,10-tetrasila[2.2]paracyclophane, the first [2.2]paracyclophane bridged by heteroatoms, has been prepared. UV, IR, and 1H- 13C- and 29Si-NMR spectral together with X-ray crystallographic data are recorded. The compound displays a strong σπ mixing between Si–Si bonds and aromatic rings as evidenced by a large red shift in UV spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…poly(methylphenylsily1ene) absorbs light at 345 nm, whereas poly(cyclohexylmethy1silylene) displays an absorption maximum at 316 nm. Studies on geometrically confined oligomeric silanes, such as cyclophanes bridged by oligosilanes, have shown that rr-a interaction can result in extended delocalization [7,8], manifest in pronounced bathochromic UV-shifts.…”
Section: Introductionmentioning
confidence: 99%
“…poly(methylphenylsily1ene) absorbs light at 345 nm, whereas poly(cyclohexylmethy1silylene) displays an absorption maximum at 316 nm. Studies on geometrically confined oligomeric silanes, such as cyclophanes bridged by oligosilanes, have shown that rr-a interaction can result in extended delocalization [7,8], manifest in pronounced bathochromic UV-shifts.…”
Section: Introductionmentioning
confidence: 99%
“…The photoelectron spectra of these compounds and that of 49 revealed variable r-p interactions between the bridges and the benzene decks [12,45,46]. Because of the long Si-Si distances, the benzene rings in 54 are less distorted than in 14, however, the compound displays strong r-p mixing between the Si-Si bonds and the aromatic rings as evidenced by a large red shift in the UV spectrum [48]. In the octafluoro derivative 52, the interaction of the p electron clouds of the aromatic rings is slightly weakened because of fluorination-induced steric hindrances [47].…”
Section: Multibridged [2 N ]Cyclophanes and Related Compoundsmentioning
confidence: 95%
“…[2 2 ](1,4)Cyclophane-1-ene (48) and [2 2 ](1,4)cyclophane-1,9-diene (49) have essentially the same UV ab- (14) was also achieved by fluorination (52), replacing them by cyclopropane rings (53) or disilane groups (54). [2 2 ](1,4)Cyclophane-1-ene (48) and [2 2 ](1,4)cyclophane-1,9-diene (49) have essentially the same UV ab- (14) was also achieved by fluorination (52), replacing them by cyclopropane rings (53) or disilane groups (54).…”
Section: Multibridged [2 N ]Cyclophanes and Related Compoundsmentioning
confidence: 99%
“…1. The structure is discussed in comparison with three closely related structures: p-bis(hydroxydimethylsilyl)benzene (II) (Alexander, Northolt & Engmann, 1967), 1,1,2,2, 9,9,10,10-octamethyl-1,2,9,10-tetrasila[2.2]-paracyclophane (III) (Sakurai, Hoshi, Kamiya, Hosomi & Kabuto, 1986) and p-bis(tetramethylsilyl)benzene (IV) (Menczel & Kiss, 1975). The Si to the phenyl-ring C bonds are in good agreement with their counterparts in (II), (III) and (IV).…”
Section: Commentmentioning
confidence: 99%